Wood Chemistry Perspectives at TalTech - Tiit Lukk (Proceedings, 2024)
Despite being the most abundant renewable resource in Estonia, wood has not been fully utilized for its potential value. To fully harness its potential, wood needs to be processed to its core components, such as fibers, wood sugars, and lignin, using chemical, thermochemical, or enzymatic methods. Researchers at TalTech are working on developing a comprehensive value chain for wood valorization, encompassing the production of food additives, thermoplastics, coating materials, and fine chemicals. Traditionally, lignin, a byproduct of the wood fractionation, was burned for energy. However, TalTech researchers are now using lignin to create novel thermoplastics, catalytic materials, and fine chemicals via fermentation processes. Here we show that the conversion of lignin into novel functional materials can be tailored by selecting appropriate extraction methods and source biomass. For instance, organosolv lignin extracted from barley straw exhibits the largest BET active surface area for lignin-based aerogels compared to those produced from softwood or hardwood organosolv lignins. Additionally, we showcase the potential of actinobacterial enzymes to detoxify phenol-containing wood sugar solutions, enabling their utilization in fermentation processes involving a wider array of microbial species.